Updates and additions to the annotated checklist of click-beetles (Coleoptera: Elateridae) of Iran - Ghahari, Hassan; Packova, Gabriela; Platia, Giuseppe; Kundrata, Robin (Zootaxa, 2024)
In this study, we provide numerous updates and additions to the checklist of click-beetles (Elateridae) of Iran based on the most up-to-date family classification as well as on the recent taxonomic studies dealing with the species diversity of the click-beetles from Iran. The updated checklist of Iranian Elateridae includes 293 species classified in 62 genera and seven subfamilies, i.e., Agrypninae (15 genera, 42 species), Cardiophorinae (six genera, 68 species), Dendrometrinae (16 genera, 35 species), Elaterinae (21 genera, 124 species), Hemiopinae (one genus, 4 species), Lissominae (one genus, two species), and Negastriinae (two genera, 18 species). The following new combinations are proposed for species hitherto included in Conoderus Eschscholtz, 1829 (since Conoderus is currently a synonym of Monocrepidius Eschscholtz, 1829): Monocrepidius posticus (Eschscholtz, 1822) comb. nov. and Monocrepidius productus (Peyerimhoff, 1931) comb. nov. The following new combinations are proposed for species hitherto included in Hemicrepidius Germar, 1839: Pseudathous agajevi (Platia, 2008) comb. nov., Pseudathous koenigi (Schwarz, 1897) comb. nov., Pseudathous nigritulus (Reitter, 1890) comb. nov., and Pseudathous rahmei (Németh & Platia, 2014) comb. nov. Approximately one third (96) of the listed species are currently endemic to Iran.